Cytomegalovirus chronic retinal necrosis with ganciclovir resistance: a case report - Julia Xia; Sanjana Kantipudi; Christopher C. Striebich; Andrés F. Henao-Martinez; Niranjan Manoharan; Alan G. Palestine; Amit K. Reddy (Journal of Ophthalmic Inflammation and Infection, 2024)
Abstract Background Cytomegalovirus (CMV) chronic retinal necrosis (CRN) is a rare viral retinal infection that occurs in mildly immunocompromised people. It shares some features with both acute retinal necrosis and CMV retinitis. It is typically treated with combination intravitreal and systemic ganciclovir. We discuss the management of a case of CMV CRN with ganciclovir resistance. Case presentation An 80-year-old female presented with one month of blurry vision in the left eye. She was being treated with abatacept, methotrexate, and prednisone for rheumatoid arthritis. Examination revealed anterior chamber and vitreous cell along with peripheral retinal whitening. Fluorescein angiogram showed diffuse retinal non-perfusion. Aqueous fluid PCR testing returned positive for CMV. The retinitis was initially controlled with oral and intravitreal ganciclovir, but then recurred and progressed despite these therapies. Ganciclovir resistance was suspected and the patient was switched to intravitreal foscarnet injections, along with oral letermovir and leflunomide, which lead to resolution of the retinitis. The patient has now continued with letermovir and leflunomide for approximately 2.5 years without reactivation of the retinitis or need for further intravitreal anti-viral injections and with adequate control of her rheumatoid arthritis. Conclusion The incidence of CMV CRN may increase in the future as the use of non-cytotoxic immunosuppressive therapies that result in relatively mild immunosuppression also increases. Treatment with ganciclovir is effective but frequently leads to resistance, as in our case. In this situation, combination therapy with letermovir and leflunomide, particularly in the setting of rheumatoid arthritis where leflunomide can also have an anti-inflammatory effect, can be considered.